PREPARATION AND EVALUATION OF RAPIDLY DISSOLVING TABLETS OF RALOXIFENE HYDROCHLORIDE BY TERNARY SYSTEM FORMATION - Maghraby, Gamal Mohamed El; Ghanem, Samar Fayez (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objectives: Enhancing the dissolution rate of raloxifene hydrochloride for the preparation of rapidly disintegrating tablets with subsequent rapid dissolution. Methods: Binary and ternary solid dispersions (SDs) with different carriers were prepared at various drug: carrier ratios including cremophor RH 40, polyvinylpyrrolidone (PVP K30), poloxamer 407 and gelucire 44/14 as carriers and were evaluated by drug content, In-vitro dissolution studies, Differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) analysis analysis. The most efficient solid dispersion was selected for preparation of rapidly dissolving tablets. Results: SDs showed enhanced dissolution rate compared to the unprocessed drug. Differential scanning calorimetry revealed that enhancement in drug dissolution was mainly due to a change in its crystalline structure. FTIR studies revealed no interaction between the drug and excipients. The dissolution pattern of the drug from the prepared tablet depended on the components of the tablets with those containing a combination of super-disintegrants (crospovidone and croscarmellose) in the presence of citric acid as channeling agent and pH modifier being the best. Conclusion: The study presented a system capable of increasing the dissolution rate of raloxifene with successful incorporation in rapidly disintegrating tablets with subsequent fast dissolution. Â  34